Coumarin: A natural solution for alleviating inflammatory disorders - Farnoosh Saadati; Amir Modarresi Chahardehi; Negar Jamshidi; Nazanin Jamshidi; Darioush Ghasemi (Current Research in Pharmacology and Drug Discovery)
Coumarin, a naturally occurring compound found in various plants, has a rich history of use in traditional medicine. Recent research has highlighted its anti-inflammatory properties, positioning it as a promising candidate for treating inflammatory disorders such as rheumatoid arthritis, asthma, and inflammatory bowel disease. This narrative review aims to comprehensively summarize the current knowledge regarding coumarin's pharmacological effects in alleviating inflammatory conditions by analyzing preclinical and clinical studies. The review focuses on elucidating the mechanisms through which coumarin exerts its anti-inflammatory effects, including its antioxidant activity, inhibiting pro-inflammatory cytokine production, and modulation of immune cell functions. Additionally, the paper addresses potential limitations of using coumarin, such as concerns about toxicity at high doses or with prolonged use. Before widespread clinical application, further investigation is needed to fully understand coumarin's potential benefits and risks.